An exploration of the causal relationship between 731 immunophenotypes and osteoporosis: a bidirectional Mendelian randomized study - Zhou, Dongqi; Zi, Changyan; Gan, Gaofeng; Tang, Shiyun; Chen, Qiu (Frontiers in Endocrinology, 2024)
Background There are complex interactions between osteoporosis and the immune system, and it has become possible to explore their causal relationship based on Mendelian randomization methods. Methods Utilizing openly accessible genetic data and employing Mendelian randomization analysis, we investigated the potential causal connection between 731 immune cell traits and the risk of developing osteoporosis. Results Ten immune cell phenotypes were osteoporosis protective factors and three immune cell phenotypes were osteoporosis risk factors. Specifically, the odds ratio (OR) of IgD+ CD24+ %B cell (B cell panel) risk on Osteoporosis was estimated to be 0.9986 (95% CI = 0.9978 0.9996, P<0.01). The OR of CD24+ CD27+ %B cell (B cell panel) risk on Osteoporosis was estimated to be 0.9991 (95% CI = 0.9984 0.9998, P = 0.021). The OR of CD33- HLA DR+AC (Myeloid cell panel) risk on Osteoporosis was estimated to be 0.9996 (95% CI = 0.9993 0.9999, P = 0.038). The OR of EM CD8br %CD8br (Maturation stages of T cell panel) risk on Osteoporosis was estimated to be 1.0004 (95% CI = 1.0000 1.0008, P = 0.045). The OR of CD25 on IgD+ (B cell panel) risk on Osteoporosis was estimated to be 0.9995 (95% CI = 0.9991 0.9999, P = 0.024). The OR of CD25 on CD39+ activated Treg+ (Treg panel) risk on Osteoporosis was estimated to be 1.001 (95% CI = 1.0001 1.0019, P = 0.038). The OR of CCR2 on CD62L+ myeloid DC (cDC panel) risk on Osteoporosis was estimated to be 0.9992 (95% CI = 0.9984 0.9999, P = 0.048). The OR of CCR2 on CD62L+ plasmacytoid DC (cDC panel) risk on Osteoporosis was estimated to be 0.9993 (95% CI = 0.9987 0.9999, P = 0.035). The OR of CD45 on CD33dim HLA DR+ CD11b- (Myeloid cell panel) risk on Osteoporosis was estimated to be 0.9988 (95% CI = 0.9977 0.9998, P = 0.031). The OR of CD45 on Mo MDSC (Myeloid cell panel) risk on Osteoporosis was estimated to be 0.9992 (95% CI = 0.9985 0.9998, P = 0.017). The OR of SSC-A on B cell (TBNK panel) risk on Osteoporosis was estimated to be 0.9986 (95% CI = 0.9972 0.9999, P = 0.042). The OR of CD11c on CD62L+ myeloid DC (cDC panel) risk on Osteoporosis was estimated to be 0.9987 (95% CI = 0.9978 0.9996, P<0.01). The OR of HLA DR on DC (cDC panel) risk on Osteoporosis was estimated to be 1.0007 (95% CI = 1.0002 1.0011, P<0.01). No causal effect of osteoporosis on immune cells was observed. Conclusions Our study identified 13 unreported immune phenotypes that are causally related to osteoporosis, providing a theoretical basis for the bone immunology doctrine.